LACAK BALAK UNTUK VERIFIKASI UJI LEGALITAS KAYU PADA PEMANENAN KAYU HUTAN ALAM - Soenarno; Satria Astana (BRIN Publishing, 2018)
Currently, timber trade requires that wood products must come from legally and responsibly managed forests. In Indonesia, to prove that wood products are legal if they are equipped with Legitimate Certificate of Forest Product, V-legal mark and electronic label in the form of Barcode. One method of proving wood origin in timber harvesting is log tracking method through labeling. This study examines the accuracy of log tracking in a Timber Forest Product Enterprise of Natural Forest (IUPHHK-HA) PT. Sumalindo Lestari Jaya II in Mahakam Ulu District, East Kalimantan Province. The log tracking was accomplished by tracking the comformity between wood documents in production result report (LHP), the numbered tree label attached on the stump till the cruising result report (LHC) document. Methods of sampling of LHP wood documents were conducted purposively through sample plots in three different felling sites. Results showed that timber traceability based on the LHP document to the tree number label attached on the tree stump wae 100%. However the level of log traceability from LHP documents to LHC documents ranges from 85.7–100% with average of 96.2%. Mismatch information between timber documents on LHP, the stump and LHC was mainly caused by wrong group of wood species and tree diameter classes.